Modern Web Visualization Concepts of Tourist Destination - Zoran Katanić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Researches in this study refer to practical application of innovative concept of visualization as a concept of tourist services through new information technologies and their impact on quality of tourist agency offer. Furthermore, the study contains a brief overview of the most frequently applied visualization tools and their basic properties. The basic research assumptions in the study are directed towards Internet presentation of commercial tourist offer, enabling spatial experience of a destination, constant availability of information, as well as usage of web and android applications which leave greater impression on potential user of the services than standard leaflets and catalogues. The presented results of analysis have shown that application of modern visualization concepts improves tourist product and visits to destinations. Thus, destinations using modern information systems on their Web sites have better presentation of tourist offer and achieve greater competitiveness on the market.
Keywords: O32; 330; visualization; development; Android applications; Web Design; innovations; modern information systems; quality